Information System for Predicting Fisheries Outcomes Using Regression Algorithm Multiple Linear - Nurdin Nurdin; Fajriana Fajriana; Maryana Maryana; Ama Zanati (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Bireuen is one of the regencies in Aceh province which has quite a lot of potential for marine and fishery resources, both capture fisheries and aquaculture, because some areas in this district are coastal areas supported by several fish landing bases (PPI), namely PPI Kuala Jangka, Kuala Jeumpa, Peudada, Jeunip, Pandrah, and Bate Iliek which are supporting sectors of the regional economy. The importance of this research is so that the Department of Food Security, Maritime Affairs and Fisheries can estimate the catch of fish in the coming year so that it can be used in terms of policies to increase the fishery production sector. The method used in information systems research to predict fishery results Multiple Linear Regression Algorithm using two independent variables (X), namely, the number of motorized boats (X1), the number of rainy days (X2) and one dependent variable, namely the number of fish caught (Y). ). The steps taken in this research are data collection, calculation of each variable, completion of the elimination method, substitution to get constant values, coefficients and inserting constants and coefficients into the Multiple Linear Regression equation. Based on data obtained from 2016, 1017, 2018, 2019 and 2020 using the Multiple Linear Regression algorithm, the prediction results of the Tangka fishery in Bireuen Regency in 2021 are 12,813.88 tons.